Low permeable composite membrane based on sulfonated poly(phenylene oxide) (sPPO) and silica for vanadium redox flow battery. (27th July 2017) - Sadhasivam, T.; Kim, Hee-Tak; Park, Won-Shik; Lim, Hankwon; Ryi, Shin-Kun; Roh, Sung-Hee; Jung, Ho-Young
Abstract: The proton conductivity and vanadium permeability of organic-inorganic (sulfonated poly (phenylene oxide) (sPPO)-nano sized sulfonated silica (sSiO2 )) hybrid membrane were investigated for application in a vanadium redox flow battery (VRFB) system. Significant attention is being paid to PPO polymers as a replacement for Nafion ® membranes due to their relatively low cost and ease of sulfonation. The attachment of a sulfonic acid (SO3 H) functional group to PPO and SiO2 was confirmed using Fourier Transform Infrared Spectroscopy (FTIR). The hybrid membrane (sPPO-2% sSiO2 ) exhibited increased thermal stability, water uptake (WU), ion exchange capacity (IEC) and proton conductivity (IC) compared with a conventional organic sPPO membrane. The proton conductivity of the hybrid membrane increased considerably compared to sPPO alone, resulting from the 2% sSiO2 nanoparticles added homogeneously to the polymer matrix. The proton conductivities of the sPPO and hybrid membranes were 0.050 and 0.077 S/cm, respectively. The increased proton conductivity of the hybrid membrane was attributed to the enhanced hydrophilic properties of SO3 H in the membranes. In addition, inorganic particles in the polymer matrix acted as a barrier for vanadium ion crossover. During VRFB unit cell operation, vanadium ion (VO 2+ ) crossovers were measured as 14.66, 1.955 and 0.173 mmol L −1 through Nafion ® 212, sPPO and hybrid membranes, respectively, and VO 2+ permeability were 2.22 × 10 −7, 2.50 × 10 −8 and 4.76 × 10 −9 cm 2 min −1 for Nafion ® 212, sPPO and hybrid membranes, respectively. Based on our experimental results, low cost organic-inorganic hybrid membranes as prepared provide an efficient alternative membrane material for advanced VRFB systems. Highlights: Novel Organic-Inorganic hybrid structured membrane for advanced VRFB system. PPO as a replacement for Nafion ® membranes due to low cost and ease of sulfonation. Proton conductivity increased to hybrid membrane (0.077 S/cm) compared to sPPO alone. VO 2+ permeability of sPPO-sSiO2 membrane is significantly lower than Nafion ® 212. sSiO2 in the sPPO polymer matrix acted as a barrier for vanadium ion crossover.